Synthesis And Thermal Conductivity Of Copper Nanoparticle Encapsulated By Graphene - Dayou, Sebastian (2017)
A facile chemical vapor deposition (CVD) method was used to synthesize graphene, which was catalyzed by copper supported on MgO. The use of graphene-CuO-MgO composite (i.e. the product after CVD) as additive for thermal conductivity enhancement in thermal energy storage material was also investigated. CuO-MgO was prepared by depositing 5 mol. % of copper nanoparticle on MgO powder using an impregnation technique. Investigation under scanning electron microscope coupled with energy dispersive X-ray spectrometry revealed that the copper nanoparticles were evenly deposited on the surface of MgO powders. The CVD process was carried out at atmospheric pressure in a horizontal fixed bed reactor without a dedicated reduction step prior to CVD reaction process; hence copper nanoparticle was in its oxidized state during the growth process of graphene. The mechanism by which graphene grows on copper oxide was deeply investigated by X-ray photoelectron spectroscopy and X-ray diffraction. For the first time, it was unambiguously proven that copper oxide (5 mol.%) efficiently catalyze the growth of few- and multi-layered graphene when the CVD reaction was conducted at 950 °C for 60 min, 980 °C for 30 min and 1000 °C for 30 min under the flow of methane (50 mL/min), nitrogen (100 mL/min) and hydrogen (100 mL/min). The mechanism of graphene growth was proposed in the following order: (i) reduction process of CuO by hydrogen that creates oxygen vacancies on the surface, (ii) methane dehydrogenation on the oxygen vacancy site and (iii) subsequent construction of graphitic network forming graphene layers. Based on the result from an alternative, direct and accurate approach of thermogravimetric analyses, high content of graphene was able to be produced (around 9.6 wt. %) when the CVD reaction was conducted at 1000°C for 30 min. Compared to the existing methods, this corresponds to a high efficiency (125 wt.%) and growth rate of graphene (42 mg/ min/ g of catalyst), produced at a considerably lower cost since cheaper raw materials were utilized. The as-produced material after CVD (i.e. graphene together with CuO-MgO) has high potential to be used in thermal energy storage applications due to the expected high thermal conductivity enhancement it could offer from the establishment of direct contact between the constituents, i.e. graphene, CuO and MgO, forming an interconnected network for heat conduction pathway. Based on the thermal investigation using a transient plane source method, 51% enhancement to the thermal conductivity of the thermal storage material was recorded.